The Privacy Price of School Safety Stakeholders' Perceptions Towards the Use of Closed-Circuit Television (CCTV) in Schools (Madhyabindu Journal, 2024)
CCTV surveillance cameras have played an influential role in safeguarding security, discipline, and a conducive learning environment in Nepali schools. However, as surveillance technology is gradually being installed and used, there is a growing concern about privacy violations. In this context, the article aims to explore the distinct perceptions and understanding of the key stakeholders, namely students, teachers and administrators, regarding using CCTV surveillance technology in their natural setting. This article especially seeks the stakeholders’ perceptions on the impact of surveillance technology on students and teachers about their privacy rights. To meet the objective, I have employed a qualitative study that follows the interpretivists’ research paradigm. I have purposively selected five respondents from each school, incorporating three students and two teaching faculties cum administrative persons. I employed semi-structured interviews at three secondary schools from inner Terai of Nawalpur district. Moreover, I utilized non-participant observation, field notes and google-form as a tool to gather content-rich data and verify the information accumulated through semi-structured interviews, regarding their lived and subjective perceptions about using CCTVs. Findings indicate effectively managing and mitigating various risk factors within schools’ premises, and cultivating a culture of shared responsibilities among students and teachers for building a conducive learning culture in schools. It is also found that surveillance technology in Nepali schools nurtures suspicion among stakeholders, along with acknowledging the importance of comprehensive policy, and students’ privacy concerns to ensure a safe and friendly learning culture.